Antimicrobial activity of multifaceted lactoferrin or graphene oxide functionalized silver nanocomposites biosynthesized using mushroom waste and chitosan. Issue 9 (30th January 2020) - Suleman Ismail Abdalla, Sundos; Katas, Haliza; Chan, Jie Yee; Ganasan, Pavitra; Azmi, Fazren; Fauzi Mh Busra, Mohd
Abstract : Biosynthesis of multifaceted silver nanoparticles using waste mushroom and chitosan. Abstract : Hybrid nanoparticles designed to exert multiple mechanisms of antibacterial action offer a new approach to the fight against pathogenic resistant bacteria. In this study, nanomaterials with the dual actions of antibacterial and anti-biofilm activities were developed using silver nanoparticles (AgNPs) functionalized with either lactoferrin (LTF) or graphene oxide (GO). AgNPs were synthesized using mushroom waste as a reducing agent and chitosan (CS) as a stabilizing agent, prior to their surface functionalization with either GO (AgGO) or LTF (Ag-LTF). The AgNPs exhibited a surface plasmon resonance (SPR) band at 430 nm, as determined by UV-vis spectroscopy, whereas the absorption of AgGO and Ag-LTF occurred at 402 and 441 nm, respectively. Particle size analysis of AgNPs, AgGO, and Ag-LTF revealed sizes of 121.5 ± 10.5, 354.0 ± 1.6, and 130.8 ± 1.2 nm, respectively. All AgNPs, Ag-LTF, and AgGO inhibited selected Gram-positive bacteria and Gram-negative bacteria with comparable antibacterial performance, as determined by the agar diffusion method. Despite the absence of antibacterial activity by GO and LTF, a synergistic effect of AgGO and Ag-LTF was observed as they had a greater activity against P. aeruginosa . Moreover, Ag-LTF did not affect cell viability and migration rate of cells, suggesting the non-toxicity of Ag-LTF. In conclusion, AgNPs, Ag-LTF, and AgGO possess antibacterial activity, which may offer an alternative for future antibacterial agents.